Determine the Prevalence of Vitamin D Deficiency in Individuals with PCOS Who are Admitted to a Tertiary Care Hospital - Monika, Bushra Begun Ramejo, Mehwish, Nazia Mushtaq, Rubab Munawar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of this research was to study vitamin D deficiency in women with polycystic ovary syndrome. Study Design: Observational/cross-sectional study Place and Duration: The study was conducted at Gynaecology & Obstetrics department of Chandka Medical Hospital, Larkana and Naimat Begum Hamdard University Hospital, Karachi during the period from June 2021 to January 2022. Materials & Methods: In this research, 88 women with polycystic ovarian syndrome between the age of 20 and 40 years participated. Patients’ data including age, body mass index, illness duration, parity and residency were recorded once they gave their permission. Vitamin D insufficiency was defined as a serum 25-hydroxy vitamin D level <20 ng/ml. SPSS 22.0 was used to analyze the data. Results: In our study majority of the patients 35 (39.8%) was aged between 26-30 years, followed by 31-35 years 25 (28.4%) patients. Mean BMI of the patients was 29.23±7.55 kg/m2. We found that 60 (68.2%) patients had vitamin D deficiency. Conclusion: According to the findings of this research, patients with polycystic ovarian syndrome had a higher than expected incidence of vitamin D deficiency. Keywords: Vitamin D, Deficiency, PCOS, Polycystic ovarian